Association of HLA alleles and haplotypes with CYP21A2 gene p. V282L mutation in the Croatian population. (5th October 2016) - Grubic, Z.; Maskalan, M.; Stingl Jankovic, K.; Zvecic, S.; Dumic Kubat, K.; Krnic, N.; Zunec, R.; Ille, J.; Kusec, V.; Dumic, M.
Abstract: The CYP21A2 mutations that are in linkage disequilibrium with particular HLA‐A, ‐B, ‐DRB1 alleles/haplotypes, cause deficiency of the 21‐hydroxylase enzyme (21‐OHD) and account for the majority of congenital adrenal hyperplasia (CAH) cases. The aim of this study was to investigate those associations with the p.V282L mutation linked to the non‐classical (NC) form of CAH among Croatians. The study included parents of patients with the NC form of CAH, positive for the p.V282L mutation ( N = 55) and cadaveric donor samples ( N = 231). All subjects were HLA‐A, ‐B, and ‐DRB1 typed and tested for the presence of the p.V282L mutation. Among parents of patients, 92.73% of subjects were positive for the B*14:02 allele and almost half of them carried the HLA‐A*33:01‐B*14:02‐DRB1*01:02 haplotype. Among cadaveric samples 77 out of 96 subjects positive for the B*14:02 allele had the p.V282L mutation. Among them, 37 were positive for the HLA‐A*33:01‐B*14:02‐DRB1*01:02 haplotype, 23 had the HLA‐A*33:01‐B*14:02‐DRB1*03:01 haplotype, 8 had the B*14:02‐DRB1*01:02 combination and 5 were carrying the HLA‐A*68:02‐B*14:02‐DRB1*13:03 haplotype. Only 4 of these subjects were positive for the B*14:02 allele. HLA‐B*14:02 was the only single allele with association that reached statistically significant P value (RR = 12.00; P = 0.0024). Haplotypes B*14:02‐DRB1*01:02 ( P < 0.001) and HLA‐A*68:02‐B*14:02‐DRB1*13:03 ( P < 0.001) as well as HLA‐A*33:01‐B*14:02‐DRB1*01:02 and HLA‐A*33:01‐B*14:02‐DRB1*03:01 showed high relative risks (RR = 45.00, RR = 41.63 and RR = 36.96, respectively). Our data support the previously documented association of the HLA‐A*33:01‐B*14:02‐DRB1*01:02 haplotype with the p.V282L mutation, but also point out a high frequency of the p.V282L mutation among Croatians with HLA‐A*33:01‐B*14:02‐DRB1*03:01 and HLA‐A*68:02‐B*14:02‐DRB1*13:03 haplotypes.